Delivery of WeChat-Based HIV Result e-Reports in Social Networks for Recruitment of High-Risk Population: Baseline Data From a Cluster Randomized Controlled Trial - Ju-Shuang Li; Yu-Zhou Gu; Feng-Su Hou; Yong-Heng Lu; Xiao-Ru Fan; Jia-Ling Qiu; Qing-Ling Yang; Jing Gu; Jing-Hua Li; Dong Roman Xu; Chun Hao (JMIR Publications, 2023)
BackgroundDisclosure of infectious disease status to social network peers can facilitate reaching and early detection among high-risk populations. In this era of social media, globally, HIV/AIDS represents a high burden of infectious disease. Thus, delivery of an HIV result e-report via social media presents a new approach that has the potential to improve contact with and enrollment of the high-risk population in research studies and routine practice. ObjectiveThis study explores the effectiveness and associated factors of a recruitment strategy (ie, WeChat-based HIV e-report delivery in social networks) on the enrollment of men who have sex with men (MSM) for an HIV testing intervention study. MethodsThis was an enrollment result analysis of an ongoing cluster randomized controlled trial (RCT) aiming to promote HIV testing among MSM. Recruitment of potential participants was based on the unit of an egocentric social network, which includes 1 core member (an offline tested ego as the recruiter) and several network members (online alters as network associates). Alters' enrollment and alters' transformation to ego-recruiters (alter-ego) were measured as outcomes. Recruitment outcomes were compared between the exchangeable and regular e-report groups of the RCT. Associated factors of both outcomes were also investigated, including sociodemographic characteristics, health behaviors, social network characteristics, e-report types, and online delivery information. Binary outcomes were modeled using logistic models, with Firth correction for rare events. Qualitative interviews were conducted to understand facilitators and barriers in detail for alter-ego as the subsequent wave's recruiter. ResultsThe e-report of 1157 egos who tested offline were delivered to 5165 alters in 3 recruitment waves; eventually, 1162 eligible alters enrolled in this RCT (response rate: 22.5%). In the exchangeable e-report group, 544 egos recruited 467 alters, of which 35 alters transformed to alter-egos (7.5%), whereas in the regular e-report group, 613 egos recruited 695 alters, of which 40 alters transformed to alter-egos (5.8%). Alters' enrollment at first wave was associated with a higher number of e-reports being forwarded by the egos. Alters' transformation to alter-egos for the subsequent wave was associated with the exchangeable e-report, higher income, being a Guangzhou resident, unprotected anal intercourse, preferring self-testing, and viewing senders' e-reports frequently. Qualitative interviews revealed that the lack of awareness of e-reports' function and inadequate access to e-reports at offline testing facilities were major barriers to alters' transformation to offline ego-recruiters. ConclusionsThe delivery of e-report was feasible in MSM social network, and the success and sustainability of online recruitment depended on high levels of familiarity among MSM with the digital tool. The HIV e-report exchange mechanism might promote MSM to test HIV offline to get their own e-report for exchange in the community. The e-report provides an innovative recruitment method with great potential to trace direct contacts for infectious diseases studies.